The organization of the actin cytoskeleton in vertical and graviresponding primary roots of maize. - Blancaflor, E B (1997)
To determine whether actin microfilament (MF) organization is correlated with differential elongation, primary roots of Zea mays cv Merit maintained vertically or reoriented horizontally for 15 to 120 min were stained with rhodamine phalloidin and examined with a confocal microscope. Root curvature was measured with a computer-controlled video digitizer. In vertical roots bundles of MFs in the elongation and maturation zone were oriented parallel to the longitudinal axis of cells. MFs in the vascular parenchyma cells were more abundant than in the cortex and epidermis. Epidermal and proendodermal cells in the meristematic region contained transverse cortical MFs. The organization of MFs of graviresponding roots was similar to that of vertical roots. Application of cytochalasin B or cytochalasin D resulted in extensive disruption of MFs in the cortex and epidermis, but only partially affected MFs in the stele. Despite the cytochalasin B-induced depolymerization of MFs, gravicurvature exceeded that of controls. In contrast, the auxin transport inhibitor N-1 naphthylphthalamic acid suppressed root curvature but had no observable effect on the integrity of the MFs. The data indicate that MFs may not be involved in the graviresponse of maize roots.